THE INFLUENCE OF DISPOSITIONAL MINDFULNESS ON WORK ENGAGEMENT: THE MEDIATION ANALYSIS OF WORKPLACE SPIRITUALITY AND ORGANIZATIONAL SPIRITUALITY, AMONG WHITE COLLAR EMPLOYEES IN BANGKOK, THAILAND - WATPRASONG, TANITA; VARMA, PARVATHY (Scholar: Human Sciences, 2022)
The primary purpose of this investigation was to investigate the impact of dispositional mindfulness on white-collar employees’ work engagement, based on Job Demands-Resources Model (JD-R model) and Person-Organization Fit Theory (P-O Fit), in doing so the mediating role of workplace spirituality (individual job resources) and organizational spirituality (organizational job resources) was analyzed. Total sample of participants was 1,014 white-collar who were non-management employees in Bangkok. The following standardized scales were used to collect data for this research: The Philadelphia Mindfulness Scale Thai version (PHLMS_TH), The Organizational Spiritual Values Scale (OSVS), Workplace Spirituality Scale (WPS), Thai Version-Job Content questionnaire (TJCQ), and the Utrecht and Work Engagement Scale-9 (UWES-9). Through structural equation modeling (SEM), direct and indirect models were developed and conducted to accomplish the research’s purpose. The evaluation and comparison of the fit of these models revealed that the indirect model was better fitting than the direct model, concluded the mediating role of workplace and organizational spirituality in proposed relationship.